BIBLIOMETRIC ANALYSIS OF ARTICLES ON PROPTECH IN THE FIELD OF REAL ESTATE SECTOR (Third Sector Social Economic Review, 2025)
This study aims to contribute to the literature by making a bibliometric analysis of 30 articles on Proptech in the Web of Science database between 2016 and 2024. Proptech; It is a concrete output of the technologies that make industry 4.0 possible. It is possible to say that with this technology, where data analytics is at the center of the real estate technologies network, real estate has turned into a service rather than a product. Research reveals that there have been significant increases in Proptech-related studies, both quantitatively and qualitatively, with Covid-19. Research conducted in America stands out; It is seen that similar studies are being carried out in Australia, Spain, Korea, Singapore, Vietnam, India and Italy. It has been determined that research generally focuses on business and economics, but also attracts attention in different fields. Analysis of keywords reveals that topics such as artificial intelligence, digital transformation, and real estate technology are considered important by researchers. As a result, it is possible to say that research in the field of Proptech continues with increasing momentum and the digitalization process in the sector is progressing rapidly. This research shows that research in the field of Proptech has a growing infrastructure and its importance is increasing. Despite this situation, literature research appears to be relatively limited. New studies to be carried out in this field; It is important for sector stakeholders to use innovative technologies more effectively. In addition, a better understanding of the developments in the sector and the effects of digital transformation will make it possible to support technological adaptation in business processes.
Keywords: Proptech; Real Estate; Real Estate technology; Real Estate 4.0; Property Management; Bibliometric Analysis